Medical and bioethical considerations in elective cochlear implant array removal - Owoc, S. (Journal of medical ethics, 2018)
Objective Cochlear explantation for purely elective (e.g. psychological and emotional) reasons is not well studied. Herein, we aim to provide data and expert commentary about elective cochlear implant (CI) removal that may help to guide clinical decision-making and formulate guidelines related to CI explantation.Data sources We address these objectives via three approaches: case report of a patient who desired elective CI removal; review of literature and expert discussion by surgeon, audiologist, bioethicist, CI user and member of Deaf community.Review methods A systematic review using three scientific online databases was performed. Included articles addressed the benefits and/or complications of cochlear implantation in young children, CI explantation with or without revision surgery and the ethical debate between the medical and Deaf communities on cochlear implantation and explantation.Conclusions The medical and audiological perspectives identify a host of risks related to implant removal without reimplantation, including risk from surgery, general anaesthesia, cochlear ossification and poor audiometric outcomes. The member of the deaf community and bioethicist argue that physicians need to guide the principles of beneficence, non-maleficence and patient autonomy. Taken together, patient desires should be seen as paramount, if the patient is otherwise fit for surgery and well informed.Implications for practice Similar to the case of device implantation, device explantation should be a multidisciplinary and collaborative decision with the patient and the family’s desires at the centre. While every case is different, we offer a CI explantation discussion to assist in clinical decision-making, patient counselling and education.